ANALISIS HUBUNGAN MODAL KERJA DENGAN NET PROFIT MARGIN PT. BASILAM INDAH KABUPATEN BATUBARA - eva Sriwiyanti (Jurakunman (Jurnal Akuntansi dan Manajemen), 2021)
Abstract This study aims to analyze the relationship between working capital and net profit margin. Descriptive quantitative method where quantitative data that has been processed, the results are described in sentences. The data analysis technique used is quantitative descriptive analysis with reference to the calculation results of working capital and net profit margin. The results of this study indicate that the value of the Current Ratio (CR) in 2017 is 2.4%. in 2018 the value of the Current Ratio (CR) increased to 3.8%. Then in 2019 the Current Ratio (CR) value again increased to 7.6%. The difference in the Current Ratio (CR) value from 2017 to 2018 is 1.4%. The difference in the Current Ratio (CR) value from 2018 to 2019 is 3.8%. This means that the value of the Current Ratio (CR) has increased every year. The value of Net Profit Margin (NPM) in 2017 is 6%. In 2018 the Net Profit Margin (NPM) value increased to 7%. Then in 2019 the Net Profit Margin (NPM) value again increased to 8%. The difference in the value of the Net Profit Margin (NPM) from 2017 to 2018 is 1%. The difference in the value of the Net Profit Margin (NPM) from 2018 to 2019 is 1%. This means that the value of Net Profit Margin (NPM) has increased every year. Keywords : Modal Kerja; Net Profit Margin,